INTEGRITAS SEBAGAI PEMODERASI PENGARUH EXPECTATION GAP PADA KINERJA AUDITOR - Sadewi, Nyoman Indah; Suputra, I D G Dharma (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the influence of expectation gap on the performance of auditors and to determine the ability of integrity in expectation gap moderating influence on the performance of auditors. The research was done at KAP Bali Province. The number of respondens taken as many as 87 people. The collection of data is done through questionnaire method, ie distribute a list of questionnaire to be filled or answered by the respondent auditor at KAP in Bali Province. Testing the hypothesis in this study using moderated regression analysis (MRA). Based on the analysis found that the expectation gap positive effect on the performance of auditors, and integrity capable of strengthening the influence of expectation gap on the performance of auditors. This indicates that the auditor has high integrity, it can heighten expectation gap so as to improve the performance of auditors.
Keywords: Kinerja Auditor, Expectation Gap, Integritas